Pemberdayaan Masyarakat Kelurahan Ardirejo Kabupaten Situbondo dalam Budidaya Selada dengan Hidroponik Vertikultur - Purnamasari, Ika; Ristiyana, Suci; Wahyu Saputra, Tri; Wijayanto, Yagus; Pusparani, Syafina; Cindy Febrian, Berlian; Lailatus Sufiaah, Annisa; Kurniawan, Bintang (Universitas Mataram, 2025)
This community service activity aims to empower residents of Ardirejo Village, Situbondo Regency, in cultivating lettuce with a vertical hydroponic system as an agricultural solution in narrow land. The vertical hydroponic system was chosen because it is efficient, land-saving, and environmentally friendly. The implementation method includes socialization, technical cultivation training, plant maintenance assistance, until the harvest stage. This activity provides direct education to the community regarding seeding techniques, plant care, nutrient management, and proper harvesting methods. The results of the activity show an increase in community knowledge and skills in hydroponic cultivation practices, as well as a growing interest in developing independent hydroponic-based farming businesses. Lettuce harvesting is carried out at the age of 35 days after sowing with good results and both consumption and economic value. This activity is expected to be the first step in creating a productive environment, supporting local food security, and improving community welfare in a sustainable manner.